Detection of myocardial viability by dobutamine stress echocardiography: incremental value of diastolic wall thickness measurement. Issue 5 (14th April 2005) - Zaglavara, T; Pillay, T; Karvounis, H; Haaverstad, R; Parharidis, G; Louridas, G; Kenny, A
Abstract : Objective: To assess the diagnostic accuracy of baseline diastolic wall thickness (DWT) alone and as an adjunct to dobutamine stress echocardiography (DSE) for prediction of myocardial viability in patients with ischaemic left ventricular (LV) dysfunction, with the recovery of resting function after revascularisation as the yardstick. Patients: 24 patients with ischaemic LV dysfunction (ejection fraction < 40%) scheduled for surgical revascularisation. Setting: Regional cardiothoracic centre. Methods: All patients underwent DSE before and resting echocardiography six months after revascularisation. DWT was measured in each of the 16 LV segments. A receiver operating characteristic (ROC) and a multi-ROC curve were generated to assess the ability of DWT alone and in combination with DSE to predict myocardial viability. Results: DWT > 0.6 cm provided a sensitivity of 80%, a specificity of 51%, and a negative predictive value of 80% for the prediction of viability in akinetic segments. DSE had an excellent specificity (92%) but a modest sensitivity (60%) in akinetic segments. A combination of improvement at DSE or DWT > 0.8 cm improved sensitivity (90% v 60%, p < 0.001) and negative predictive value (92% v 78%, p  =  0.03) in akinetic segments compared with DSE alone. This was achieved with some loss in specificity (75% v 92%, p  =  0.01) and positive predictive value (71% v 82%, p  =  0.79). Conclusions: DWT measurement may improve the sensitivity of DSE for the detection of myocardial viability. Akinetic segments with DWT > 0.8 cm have a good chance of recovery despite the absence of contractile reserve during DSE. Further testing may be required before excluding myocardial viability in these cases.